Odpowiedzi

2010-02-07T10:15:39+01:00
A) 2+(-6)= -4
-21+17= 4
-3+(-8)= -11
7+(-8)= -1
15+(-2)+12 = 25
-8+(-6)+(-3)= -17
b)8-12= -4
-14-6 = -20
-24-47= - 71
7-(-8)= 15
-15-(-6)= -9
-23-(-8)= -15
c)6+(-8)-4= -6
15+(-7)-(-2)= 10
5-12-(-27)= 20
-5-(-13)+(-11)= -3
-12-23-41= -76
-14-6+(-18)= -38
2010-02-07T10:16:37+01:00
A) 2+(-6)=2-6=-4
-21+17=-4
-3+(-8)=-3-8=-11
7+(-8)=7-8=-1
15+(-2)+12=15-2+12=13+12=25
-8+(-6)+(-3)=-8-6-3=-17
b)8-12=-4
-14-6=-20
-24-47=-71
7-(-8)=7+8=15
-15-(-6)=-15+6=-9
-23-(-8)=-23+8=-15
c)6+(-8)-4=6-8-4=-6
15+(-7)-(-2)=15-7+2=10
5-12-(-27)=15-12+27=30
-5-(-13)+(-11)=-5+13-11=-3
-12-23-41=-76
-14-6+(-18)=-14-6-18=-38
pozdrawiam i chciałam zaznaczyć, że w rozwiązaniu które jest przede mną są błędy
2010-02-07T10:17:56+01:00
-4
-4
-11
-1
25
-17

-4
-20
-71
15
-9
-15

-6
10
20
-3
-76
-38